2007
DOI: 10.1245/s10434-007-9449-x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Mastectomy in BRCA1/2 Mutation Carriers and Women at Risk of Hereditary Breast Cancer: Long-Term Experiences at the Rotterdam Family Cancer Clinic

Abstract: Background: BRCA1/2 mutation carriers and women from a hereditary breast(/ovarian) cancer family have a highly increased risk of developing breast cancer (BC). Prophylactic mastectomy (PM) results in the greatest BC risk reduction. Long-term data on the efficacy and sequels of PM are scarce.Methods: From 358 high-risk women (including 236 BRCA1/2 carriers) undergoing PM between 1994 and 2004, relevant data on the occurrence of BC in relation to PM, complications in relation to breast reconstruction (BR), mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
73
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 38 publications
1
73
0
6
Order By: Relevance
“…Deze preventieve behandeling is de meest effectieve methode om een mammacarcinoom te voorkomen bij vrouwen met een verhoogd risico. Uit onderzoeken blijkt dat hiermee dit risico kan worden verlaagd tot minder dan 2% over het hele leven (Rebbeck et al, 2004;Heemskerk-Gerritsen et al, 2007;Kaas et al, 2010). De resultaten van deze behandeling zijn echter afhankelijk van de volledige verwijdering van al het klierweefsel (Willemsen et al, 1998).…”
Section: Erfelijkheidunclassified
See 1 more Smart Citation
“…Deze preventieve behandeling is de meest effectieve methode om een mammacarcinoom te voorkomen bij vrouwen met een verhoogd risico. Uit onderzoeken blijkt dat hiermee dit risico kan worden verlaagd tot minder dan 2% over het hele leven (Rebbeck et al, 2004;Heemskerk-Gerritsen et al, 2007;Kaas et al, 2010). De resultaten van deze behandeling zijn echter afhankelijk van de volledige verwijdering van al het klierweefsel (Willemsen et al, 1998).…”
Section: Erfelijkheidunclassified
“…Sinds 1994 zijn de BRCA1-en BRCA2-genmutaties bekend die het levenslange risico op een mammacarcinoom kunnen verhogen tot ongeveer 60-85%. Recent is dit risico iets lager geschat, namelijk 47-66% voor dragers van de BRCA1-en 40-57% voor dragers van de BRCA2-genmutatie (Heemskerk-Gerritsen et al, 2007). Dit betekent dat een jonge, vruchtbare vrouw met een BRCA1-of BRCA2-genmutatie ongeveer een jaarlijkse kans op borstkanker heeft van 2% (vanaf haar dertigste levensjaar).…”
unclassified
“…[16][17][18] Improved surgical techniques, including reconstruction, may have contributed to the 12 % per year increase in bilateral prophylactic mastectomy observed in the United States during the last decade. 19 Bilateral prophylactic mastectomy with reconstruction is a major surgical procedure, and although some have reported very low complication rates, 20 the bulk of available data suggest that 8-64 % of women will experience one or more complications [21][22][23][24] and that 52-71 % will require reoperation. [24][25][26] Prophylactic mastectomy also has a significant impact on body image and psychosocial function.…”
mentioning
confidence: 99%
“…19 Bilateral prophylactic mastectomy with reconstruction is a major surgical procedure, and although some have reported very low complication rates, 20 the bulk of available data suggest that 8-64 % of women will experience one or more complications [21][22][23][24] and that 52-71 % will require reoperation. [24][25][26] Prophylactic mastectomy also has a significant impact on body image and psychosocial function. One study found that even after completion of reconstruction, 37 % of women reported that their breasts felt unpleasant, 29 % were not satisfied with their breast appearance, and 21 % felt embarrassed for their naked bodies.…”
mentioning
confidence: 99%
“…reconstructive techniques can be classified into autologous and implant-based reconstruction as well as a combination of the two. A wide scale of differing complication rates has been reported in various studies (5,(8)(9)(10).…”
mentioning
confidence: 99%